1981
DOI: 10.1159/000128209
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Insufficiency in the Rat after Intravascular Coagulation and Inhibition of Fibrinolysis

Abstract: Thrombin-induced intravascular coagulation was followed by pulmonary dysfunction in rats treated with the fibrinolysis inhibitor AMCA (trans-4-aminoethyl-cyclohexane carboxylic acid). The pulmonary dysfunction developed after a latency period of about 60 min and led progressively to pulmonary insufficiency with a morphological and functional pattern similar to that in the human delayed microembolism syndrome. Neither activation of the kallikrein-kinin system nor inhibition of converting enzyme activity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The findings reported above indicate that pulmonary insufficiency fol lowing pulmonary microembolism of fibrin in the rat [6] is characterized by very distended lymph vessels and profound accumulation of highly proteinrich fluid in the lungs. These features point to an increased lymph transport and enhanced microvascular permeability to macromolecules.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The findings reported above indicate that pulmonary insufficiency fol lowing pulmonary microembolism of fibrin in the rat [6] is characterized by very distended lymph vessels and profound accumulation of highly proteinrich fluid in the lungs. These features point to an increased lymph transport and enhanced microvascular permeability to macromolecules.…”
Section: Discussionmentioning
confidence: 85%
“…We have shown previously that in spite of a general fibrinolysis inhibi tion a local increase in FDP occurs in the lung tissue of thrombin-injected rats [6], In other studies it has been found that FDP increase microvascular permeability [5] and it can also be concluded that the mechanical effects of microembolism alone cannot explain the profound pulmonary oedema resulting in this model [9]. We therefore attempted to determine whether locally released FDP could have played a role in the development of the pulmonary oedema.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations